People from the road. (Journal of Parents and Teachers, 2014)
The integral development of people belongs to each and every one of us who, as people of the path of life that we are, we must realize ourselves by helping others and being in solidarity with them.
Keywords: Integral development; realization; being authentic; values; solidarity.